Patchy Lakes and Topographic Origin for Fast Flow in the Recovery Glacier System, East Antarctica. Issue 2 (1st February 2019) - Diez, Anja; Matsuoka, Kenichi; Jordan, Tom A.; Kohler, Jack; Ferraccioli, Fausto; Corr, Hugh F.; Olesen, Arne V.; Forsberg, René; Casal, Tania G.
Abstract : The Recovery subglacial basin, with its largest glacier Recovery Glacier, has been identified as potentially the biggest contributor to future sea level rise from East Antarctica. Subglacial lakes along the main trunk have been detected from satellite data, with four giant lakes (Recovery Lakes A, B, C, and D) located at the onset of the fast ice flow (≥15 m/yr) and multiple smaller lakes along the glacier. The presence of subglacial water potentially plays a key role in the control of fast ice flow of Recovery Glacier. We present new insights on the Recovery Lakes from airborne radar data collected in 2013 and 2015. Using an adjusted classification scheme, we show that a single large area consisting of smaller lakes connected by likely saturated sediment, referred to as Lake AB, exists in the originally proposed area of the Recovery Lakes A and B. We estimate that the current size of Lake AB is ∼4, 320 km 2 . Water likely leaks from the western shore of Lake AB lubricating the bed initiating fast ice flow at this location. The difference in the outlines of Lake AB and the Lakes A and B previously derived from surface features suggested that a larger paleolake existed here in the past. From our data, we find Recovery Lake C to be dry; we attribute fast ice flow originating from this area to be due to a topographic step and thus an increase in ice thickness rather than enhanced lubrication at the bed. Plain Language Summary: Lakes of liquid water exist under the Antarctic ice sheet. The lake surface is very smooth, and the ice can easily slide over it. This is reflected in a very smooth ice surface, which can be detected in satellite images. To gain more detailed information about subglacial lakes, we need to look below the ice. This is possible with radar waves that travel through the ice where they are reflected at the interface between ice and bedrock or ice and water. Analyzing the reflected signal strength, we derive information about the conditions at the bed and can detect water. Four giant lakes (Recovery Lakes A–D) were identified from satellite data at the onset of fast ice flow of Recovery Glacier. Analyzing a 10‐km grid of radar data over these lakes, we now show that Lakes C and D are dry and only one lake exists in the area of the proposed Lakes A and B. This one lake likely regulates the fast ice flow of Recovery Glacier by water leakage from the lake shore. Key Points: Automatic classification reveals patchy lake area at onset of Recovery Glacier The main ice flow branch of Recovery Glacier is likely initiated through leakage of water from the lake area Fast ice flow originating at the dry Lakes C and D is triggered by a topographic step